(untitled) - Green, Robert (Indianapolis, Ind., 2007)
Get the strategies you need for successful CAD management in this one-of-a-kind resource. You’ll learn basics such as how to assign tasks, set budgets, and formulate ROI-and gradually delve into more complex issues such as managing intellectual property, selling ideas to management and end users, and configuring for specific engineering environments. This indispensable resource is packed with savvy insights, practical techniques, and real-world advice to broaden your technical, business, and management skills.
Keywords: Engineering design,Computer-aided design,Kỹ sư thiết kế,Máy tính hỗ trợ thiết kế; Data processing,Management,Xử lý dữ liệu,Quản trị